Administrative Corruption in Contemporary Systems and the Role of Islamic Administrative Organization in Combating It - Abdul Hadi, Sarmad (Journal of Legal Sciences, 2023)
Administrative corruption is a concept that includes the abuse of entrusted power for personal benefit. It has become a prominent contemporary problem affecting all government systems around the world. It involves widespread harm and negative impact on progress and development, and is considered a threat at the international level because it impedes development programs and undermines the interests of the public. Administrative corruption threatens modern governments, distorts public policies, causes weaknesses in the oversight system, and affects the distribution of resources.Islamic law is considered a pioneer in diagnosing this type of problem, as it provides clear solutions to eliminate administrative corruption, as Islamic law recommends the application of oversight as a basic strategy to correct management procedures and achieve justice and equality. It also recommends that strong ethical leaders, who are considered good role models, be appointed to appropriate roles, as they will be an effective tool to reduce administrative corruption.